PENGARUH IMPLEMENTASI APLIKASI SISTEM KEUANGAN DESA, KOMPETENSI SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERN, DAN TRANSPARANSI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DESA (Studi kasus pada Desa di kecamatan Pakem kabupaten Sleman) - Teguh Erawati; Antonius Sahaduta Hamanay (JURNAL AKUNTANSI, 2022)
This study aims to examine the effect of implementing village financial system applications, human resource competencies, internal control systems, and transparency on the quality of village government financial reports. The population in this study is the village government in Sleman district which consists of 17 sub-districts and 86 villages. The sample in this study was determined using the proposive sampling method, namely 50 respondents who were village officials in all village governments in Pakem sub-district, Sleman district, who were directly involved in preparing village government financial reports. The type of data used in this research is primary data by distributing questionnaires. The data analysis method used is data quality test, classical assumption test, and hypothesis testing. The results in this study state that the simultaneous implementation of village financial system applications, human resource competencies, internal control systems, and transparency each have a positive and significant effect on the quality of village government financial reports.